Deskripsi Kemampuan Hasil Lari 100 Meter - fastabiqul khoirot; touvan Juni Samodra; Eka Supriatna (Fakultas Pendidikan Olahraga dan Kesehatan, Universitas Pendidikan Indonesia, 2022)
The study aims to description of the ability of men's and women's running speed to the results of the 100-meter sprint. This research is descriptive quantitative, with a survey with a 100-meter test. The population in this study were students of the 2021 Class of Sports Coaching Education with 33 people. The data analysis technique uses percentage statistics. The results showed that the average running ability of men was 14.74 seconds, with the fastest running 13 seconds and 16.69 seconds late. For the daughter of 8 students, the fastest 17.87 seconds was 19.90 seconds late with an average acquisition of 18.50 seconds.